Blood biocompatiblity of polyvinyl, chloride surface-modified with multi-walled carbon nanotubes - Gaffney, Alan Michael (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2012)
Blood-surface interaction in extracorporeal circuits (for example, cardiopulmonary bypass) requires the infusion of a systemic anticoagulant to prevent devastating thrombus formation. Platelet activation upon contact with foreign circuit surfaces is the primary mechanism underlying thrombus formation. Research into nano-enabled approaches to blood-surface biocompatibility is at a very preliminary stage, however, carbon nanotubes are being developed as potential modulators of blood-surface biocompatibility. The general objective driving this research was to study the effects of nanomodification of medically relevant surfaces on blood biocompatibility. For the purpose of my PhD research, I hypothesised that the modification of polyvinyl chloride surfaces with carbon nanotubes affects blood biocompatibility. The specific aims explored in this investigation focused on studying the effects of polyvinyl chloride surface-bound carbon nanotubes on platelet function in in vitro (using the quartz crystal microbalance with dissipation flow model, platelet aggregometry, scanning electron microscopy, and phase contrast microscopy) and in vivo (rabbit) models of extracorporeal circulation. Furthermore, the platelet biocompatibility of polyvinyl chloride- carbon nanotube surfaces functionalised with a potent antiplatelet drug, iloprost, was investigated using the above in vitro techniques as well as mass spectrometry. Finally, proteomics and surface protein adsorption experiments (using the quartz crystal microbalance with dissipation flow model, platelet aggregometry and ELISA) were used to study the mechanisms of nanomodified surface-platelet interactions.
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin